A Discussion on Chinese Road of NGOs : Reform and Co-governance by Society - Wang, Ming (Springer Nature, 2017)
This book reflects the author's views on NGO development in China and includes recent papers, reviews, and policy suggestions he has written. This collection introduces the current state of research on NGOs and their development in China to an English-speaking audience, allowing them to understand China's social reforms, which center on NGOs.
Keywords: Non-governmental organizations -- China -- Management.; China -- Social policy.; China -- Economic policy.; China.; elektronické knihy; electronic books